Comprehensive Review of Healthcare Policy Reforms and Lessons from Global Systems - Alraboa, Ali Nasser Ali; Alraboo, Saeed Nasser Ali; Al yami, Faleh Merja Dwwas; Abuod, Saad Saeed; Almshaly, Shima Abdulla; Al Abbas, Makki Yahya Mohammed; Al Rawas, Rawas Ali Saleh; Al-Saed, Saleh Mohsen Ali; Aljafar, Fares Mana Hussaen; Al Abbas, Mohammed Saleh Zidane (Journal of Ecohumanism, 2024)
The issues of cost containment, financing, accessibility of health services and the general quality of health services remain global concerns for all healthcare organizations. With these challenges rising, most countries have adopted various healthcare policy reforms to increase efficiency and availability and lower the cost of healthcare policies. This paper brings together a physician’s perspective on what has already been learned regarding healthcare policy reform in the US and other industrialized countries, such as the UK and Scandinavian countries, to draw from the experiences of these countries to inform similar countries. In the USA, the ACA brought new changes in coverage and healthcare access, but it brought a lot of political controversy. In this context, the case of the United Kingdom with NHS still provides lessons regarding government-funded systems for UHC. Halsted, a city in Sweden, along with Denmark and Norway, has integrated care systems, which put stress on the primary care settings and preventive care. In addition, this paper evaluates the trends in low- and middle-income countries' healthcare reforms with an emphasis on improving access for these underserved populations through collaborations with international facilities. The study implies that hallmark characteristics of healthcare reforms are political commitment, digitized health sectors, and the engagement of different stakeholders. This paper discusses recommendations for further reforms concerning technology, primary care, and global health collaboration to improve equity and efficiency in health care.